2015
DOI: 10.1016/j.jebo.2015.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Investment liberalisation, technology take-off and export markets entry: Does foreign ownership structure matter?

Abstract: Abstract:Before and after its accession to the WTO in 2001, China has undergone a far-reaching investment liberalisation. As part of this, existing restrictions on foreign ownership structure and mandatory export and technology transfer requirements imposed on foreign firms have been lifted in a number of industries. Against this background we identify the causal effects of foreign acquisitions on export market entry and technology take-off and evaluate whether the level of foreign ownership plays a role in st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 39 publications
1
19
1
1
Order By: Relevance
“…This supports the contention that foreign acquisitions tend to increase investment in R&D in host countries. Girma et al (2015) point out that to accelerate the pace of technological advancement from abroad, the Chinese government gives a number of incentives to foreign firms engaged in innovative acquisitions and this has led to increase in R&D activities in China. We expect that foreign acquisitions should have positive impact on R&D budgets and this lead to our third hypothesis.…”
Section: Alleviation Of Financial Constraints; Randd and Productivitymentioning
confidence: 99%
“…This supports the contention that foreign acquisitions tend to increase investment in R&D in host countries. Girma et al (2015) point out that to accelerate the pace of technological advancement from abroad, the Chinese government gives a number of incentives to foreign firms engaged in innovative acquisitions and this has led to increase in R&D activities in China. We expect that foreign acquisitions should have positive impact on R&D budgets and this lead to our third hypothesis.…”
Section: Alleviation Of Financial Constraints; Randd and Productivitymentioning
confidence: 99%
“…22 This approach enables us to include the 19 Propensity score matching (without regression adjustment) has been quite popular in the literature on foreign ownership; see, for example, Arnold and Javorcik (2009) and Girma and Görg (2007). Guadalupe et al (2012) and Girma et al (2015) provide examples of a propensity score reweighting approach combined with regression adjustment. 20 The exact variables used are as follows: k30 contains the value for the answer to the "access to finance" obstacle question.…”
Section: Empirical Methodology and Datamentioning
confidence: 99%
“…() and Girma et al. () provide examples of a propensity score reweighting approach combined with regression adjustment.…”
mentioning
confidence: 99%
“…Study done by [1] indicate that domestic firms are more export-oriented when compared to foreign-owned subsidiaries.Study [2] found a positive correlation between foreign ownership and export behaviour of large firms in India. Study [15] shows that macroeconomic factors like liberalization, technology and innovation have a positive influence on export intensity with respect to foreign ownership firms. They found strong yet heterogenous positive influence on foreign ownership structure firms using bivariate probit regression analysis method.…”
Section: ) Ownership Structurementioning
confidence: 97%